Monitoring of River Ram Ganga: Physico-chemical Characteristic at Bareilly - Manoj Gupta2 and Adarsh Pandey3, Ramesh Chandra1 (Recent Research in Science and Technology, 2011)
Ranganga is an important river in U.P., it originates from the hills of Garhwal and traverses through Kalagarh, Moradabad and Bareilly and finally merges into Ganga at Farukhabad, covering a distance of about 480 km. An attempt has therefore been made to study the magnitudes of pollution because it was observed that the sewage disposal and large number of industries of river Ramganga .There is significant difference in temperature (46%) in the winter and summer season. The water was colorless at upstream side but becomes blackish at downstream at the junction of Sankha River.Ã‚Â  pH of river ranged from a minimum 7.28 at station No.I to a maximum 8.6 at station No.II. Dissolved oxygen ranged from 3.8 ppm at station No. II in summer season to 5.4 ppm. There was no significant change in total alkalinity at station No. I in different season. However, there was a marked difference when the values are compared at station I and II. The maximum difference of 32.7% was observed in the summer season at station I and II. The hardness of water is not a pollution parameter, but indicates the water quality mainly in terms of Ca++ and Mg++ ions. The values range from 182.1 mg/l to maximum 203 mg/l at station No. II.